2008
DOI: 10.1093/molbev/msn102
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the Gene for Chloroplast RPS16 Was Assisted by Generation of a Dual Targeting Signal

Abstract: Organelle (mitochondria and chloroplasts in plants) genomes lost a large number of genes after endosymbiosis occurred. Even after this major gene loss, organelle genomes still lose their own genes, even those that are essential, via gene transfer to the nucleus and gene substitution of either different organelle origin or de novo genes. Gene transfer and substitution events are important processes in the evolution of the eukaryotic cell. Gene loss is an ongoing process in the mitochondria and chloroplasts of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 50 publications
2
113
0
2
Order By: Relevance
“…The occurrence of gene substitution implies the emergence of a nuclear-encoded counterpart of the organellar protein. The onset of cp rps16 gene substitution is minimally estimated at 140-150 mya (Ueda et al, 2008). Considering the time of divergence of Arabidopsis thaliana and O. pumila, the nuclear genome gained an rps16 copy ~140 mya, and the chloroplast and nuclear copies have coexisted (perhaps redundantly) since then.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of gene substitution implies the emergence of a nuclear-encoded counterpart of the organellar protein. The onset of cp rps16 gene substitution is minimally estimated at 140-150 mya (Ueda et al, 2008). Considering the time of divergence of Arabidopsis thaliana and O. pumila, the nuclear genome gained an rps16 copy ~140 mya, and the chloroplast and nuclear copies have coexisted (perhaps redundantly) since then.…”
Section: Discussionmentioning
confidence: 99%
“…RPS16 is essential for cell viability (Persson et al, 1995) and plays an important role in the assembly of the 30S subunit (Held and Nomura, 1975) in Escherichia coli. It was demonstrated that chloroplast-encoded (cp) rps16 has been replaced with the nuclear-encoded rps16 which had originated from the mitochondria in M. truncatula and Populus alba, and that the present status of the rps16 gene substitution in the chloroplast genome corresponds to the intermediate stage in most angiosperms (Ueda et al, 2008). This is interesting evidence of the process of gene substitution in eukaryotes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The complex evolution of rps16 is an illuminating case of both functional gene transfer and substitution. In some lineages, the mitochondrial rps16 is functionally expressed in the nucleus but absent from the mitochondria (functional transfer) while in a subset of taxa, the chloroplast copy is also absent and the nuclear gene is also targeted to the chloroplast [substitution (Ueda et al 2008b)].…”
mentioning
confidence: 99%
“…Alguns estudos especulam que as proteínas de DD evoluíram a partir de proteínas direcionadas para um único destino (UEDA et al, 2008). Neste contexto, o ganho do DD seria um mecanismo restritivo comparado ao direcionamento a uma única organela para evitar a perda do direcionamento para uma das organelas (CHEW; WHELAN, 2003;MICHALECKA et al, 2003).…”
Section: Localização Subcelular E Duplo Direcionamentounclassified